Analisis Sistem Akuntansi Persediaan Barang Dagangan Pada RE Mart Politeknik Elpetigai Tasikmalaya - Kurniawati, Ria; Kurniawan, Rudi; Dadan Suhendar, Asep (EKOBIMA, 2025)
This research is written in the final assignment which aims to determined how the implementation of the Merchandise Inventory Accounting System Analysis is applied at RE MART of the Elpetigai Polytechnic Tasikmalaya. To obtain the necessary data, the authors use data collection tools in the form of interviews, observations and literature. The data analysis method used is descriptive qualitative. From the results of this study, it can be concluded that the existing system at the RE MART of the Elpetigai Polytechnic Tasikmalaya as a whole has been implemented properly in accordance with the standard iin the theory of literature. It is also necessary to improve adequate records, document and human resource system.